1978
DOI: 10.1039/dt9780000423
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance spectra of trigonal-prismatic bis[pentane-2,4-dione benzoylhydrazonato(2—)]vanadium(IV) and bis[4-phenylbutane-2,4-dione benzoylhydrazonato(2—)]vanadium(IV)

Abstract: Electron Spin Resonance Spectra of Trigonal-prismatic Bis[pentane-2,4dione benzoylhydrazonato(2--)]vanadium(iv) and Bis[4-phenylbutane-2,4-dione benzoylhydrazonato(2-)]vanadium( IV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…For a distorted octahedral V IV O complex, such as [VO(H 2 O) 5 ] 2+ , the energy order of the five V‐d orbitals is d xy < d xz ≈ d yz < d x ²– y ² < d z ² , the singly occupied molecular orbital (SOMO, which coincides with the HOMO) being the d xy orbital. For a non‐oxido V IV species with a hexacoordinate geometry distorted toward the trigonal prism, a significant mixing of V‐d xy with the unoccupied orbitals, such as V‐d xz , V‐d yz , V‐d x ²– y ² and V‐d z ² , is expected , . Such a mixing causes a lowering of the absolute value (experimentally measured) of the 51 V hyperfine coupling constant along the x or z axis.…”
Section: Resultsmentioning
confidence: 97%
“…For a distorted octahedral V IV O complex, such as [VO(H 2 O) 5 ] 2+ , the energy order of the five V‐d orbitals is d xy < d xz ≈ d yz < d x ²– y ² < d z ² , the singly occupied molecular orbital (SOMO, which coincides with the HOMO) being the d xy orbital. For a non‐oxido V IV species with a hexacoordinate geometry distorted toward the trigonal prism, a significant mixing of V‐d xy with the unoccupied orbitals, such as V‐d xz , V‐d yz , V‐d x ²– y ² and V‐d z ² , is expected , . Such a mixing causes a lowering of the absolute value (experimentally measured) of the 51 V hyperfine coupling constant along the x or z axis.…”
Section: Resultsmentioning
confidence: 97%
“…As mentioned in the Introduction, EPR spectra of hexacoordinated V IV complexes can be divided into those with A z ≫ A x ≈ A y (geometry close to the octahedron) and those with A x ≈ A y ≫ A z (geometry close to the trigonal prism). 28 Therefore, if the axis with the highest symmetry is the z axis, in the transformation from an octahedron to a trigonal prism, the largest value of A changes from A z to A x (this is due to the elements in the diagonalized tensor A D : A z D , the highest value of the tensor, is negative in the first case and adds to A iso , whereas it is positive in the second case and subtracts from A iso ). When an anisotropic spectrum is considered, the most important datum is the highest value of A, A x or A z , depending on the type of spectrum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…24b In the literature, EPR spectra of hexa-coordinated V IV complexes were divided on the basis of g and A values: those with g z ≪ g x ≈ g y < 2.0023 and A z ≫ A x ≈ A y with a geometry close to an octahedron and those with g x ≈ g y ≪ g z ≈ 2.0023 and A x ≈ A y ≫ A z with a geometry that approaches the limit represented by the trigonal prism. 28 With bidentate ligands forming fivemembered chelate rings such as o-catechols, o-mercaptophenols, and dithiolenes, the geometry is close to the trigonal prism and there is a change of the ground state from predominant occupation of V-d xy by the unpaired electron, characteristic of V IV O species, to the occupation of other V dorbitals. 29 We recently demonstrated that, for tridentate ligands with meridional coordination, the first type of spectrum with g z ≪ g x ≈ g y < 2.0023 and A z ≫ A x ≈ A y is observed, 30 whereas, for those with facial coordination, an intermediate spectrum is detected.…”
Section: ■ Introductionmentioning
confidence: 99%
“…71 In particular, the change in the EPR behavior has been related to the switch of the ground state from d xy to d z 2 , depending, in its turn, on the transformation of an octahedron toward a trigonal prism. 18d,29, 72 We recently demonstrated that, for a tridentate ligand that forms nonoxido V IV species, mer isomers show type 1, whereas fac isomers show a type 2 spectrum.…”
Section: ■ Experimental and Computational Sectionmentioning
confidence: 99%
“…For a nonoxido V IV species with a hexacoordinated geometry distorted toward a trigonal prismatic one, an increasing mixing of d xy with the excited orbitals, such as d xz , d yz , and d z 2 , is expected. 71 The analysis of the electronic structure and molecular orbital composition for compounds 1−3 has been carried out choosing a coordinate system in which the N−V−N direction is oriented along the z-axis, and two S−V−O directions roughly occupy the x-and y-axes. The energy levels of the molecular orbitals (MOs) derived from V-d orbitals are shown in Scheme 3.…”
Section: ■ Experimental and Computational Sectionmentioning
confidence: 99%